Analysis of rheological properties of fibre suspensions in a Newtonian fluid by direct fibre simulation. part1 : rigid fibre suspensions - Yamato, Masayuki (2010)
The presentworkpresents a predictive direct fibre simulator for concentrate fibre suspension basedonthe Particle Simulation Method (PSM), considering near-field hydrodynamic interactions and collision forces to prevent fibres from overlapping. To validate the software, rheological properties such as the intrinsic viscosity [ ], the shear viscosity at steady state for various fibre concentrations and aspect ratios, and both the time transient viscosity + and time transient first normal stress difference N+ 1 under shear are discussed by comparing theories and experimental data available in the literature. It is confirmed that the software developed in this work is able to predict and analyze rheological properties quantitatively as well as qualitatively. Finally, +, N+ 1 and the second-order orientation tensor, a2, are discussed for a variety of aspect ratio and concentrations up to large strains.